Active Regulation of On‐Demand Drug Delivery by Magnetically Triggerable Microspouters. (27th December 2016) - Shademani, Ali; Zhang, Hongbin; Jackson, John K.; Chiao, Mu
Abstract : Triggerable devices capable of on‐demand, controlled release of therapeutics are attractive options for the treatment of local diseases because of their potential to enhance therapeutic effectiveness with reduced systemic toxicity. Here, the design and fabrication of a miniaturized device, termed a microspouter, is described. This device is shown to provide active and precise control of localized delivery of drugs on demand. The microspouter is composed of a magnetic sponge to provide the force for drug release through magnetic field‐induced reversible deformation, a reservoir for the sponge installation and drug loading, and a soft membrane for sealing the device. Following application of a magnetic field to the microspouter, the shrinking of the sponge may trigger a spouting of drug through a membrane's microaperture. The efficiency of the device in controlling the dose and time course of drug release under different external magnetic fields has been demonstrated using methylene blue and docetaxel as model drugs. Additionally, the microspouter is found to have low background drug leakage that allows for tunable drug release in an ex vivo implantation experiment. All the results confirm the microspouter as a potential device for safe, long‐time, and controlled drug release in local disease treatment. Abstract : A triggerable device, termed a microspouter, is designed and fabricated for active and precise control of localized drug delivery. It is able to be triggered to spout drug solution on demand through external magnetic stimuli to achieve a safe and long‐time controlled drug release.